An Exploration of Students’ Misconceptions about the Concept ‘Classification of Animals’ at Secondary Level and Effectiveness of Inquiry Method for Conceptual Change - Anjum NAZ; Abida NASREEN (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
Research has provided overwhelming evidence that children enter in science classroom with ideas they have formed in making sense of the world around them. Children observe world with curiosity which help them to construct their initial ideas (Anderson, Reynolds, Schallert & Goetz, 1977). These ideas of the child are called pre-existing knowledge which serves as a podium from which learners understand their world (Dole & Sinatra’s 1998). Similarly the children have multiple experiences of different phenomena like push, pull, throw or pull (Driver, Squires, Rushworth & Wood-Robinson, 1994). The children’s observation, ideas and experiences collectively make their preconceptions. This study was an attempt to find out misconceptions of biology students at secondary level (Wiser & Amin, 2002). It is a well known fact that students enter in science classroom with many misconceptions (Yensin 2004). This research was aimed to identify and rectify the misconceptions of students, about selected concept of biology e.g. classification of animals. The nature of the research study was exploratory. A well established technique ‘Interview about Instances’ (IAI) was used to explore conceptions and misconceptions of the students. Twenty instance cards (twenty for selected biology concept) were developed to present examples and non - examples of particular concepts in the form of diagram, line diagrams and pictures. Interviews were audio-taped with the permission of respondents and transcribed with the help of experts. A wide variety of misconceptions were found in the responses of the students therefore keeping in view the misconceptions of students inquiry sessions were planned. Whole sample of the study was randomly divided into two groups’ i.e. Group A & Group B. Group B participated in inquiry sessions while group A was kept outside. Researcher facilitated the inquiry sessions. Students planned activities and explored the concepts. Afterwards, the same instance cards were shown to both groups A & B. IAIs were conducted, recorded, transcribed and coded. The responses of students were divided into major and minor categories. The frequencies and percentages of responses given by students in pre and post session interviews were calculated and compared. In a result three categories of responses emerged such as scientific responses, misconceptions and generalizations. Moreover, to establish the effectiveness of inquiry approach as a conceptual change instructional strategy the percentages and frequencies of the responses of Group A. & B. in post session were also compared. The improvement in scientific responses and correctness of misconceptions was observed in the responses give n by group B in post session interviews. This research study concluded that students had misconceptions in very basic biological concepts. The misconceptions found were very dynamic in nature. The misconceptions of students can be addressed with appropriate conceptual change instructional strategy such as inquiry approach